What bacterial pathogens are responsible for nursing home‐acquired pneumonia?. Issue 6 (June 2015) - Mayo, Russell; Esteva, Irina; Viegas, Mark
Abstract : Evidence‐Based Answer : Streptococcus pneumoniae is the most common bacteria isolated from nursing home patients hospitalized with pneumonia (36%‐58%). Less common organisms include Enterobacteria, Legionella, Staphylococcus aureus, and Pseudomonas species (SOR: B, observational studies).